Pengembangan Model Peramalan Hama Penggerek Polong (Maruca Testulatis) Pada Tanaman Kacang Hijau - Anik Kurniati (Universitas Wiralodra, 2021)
Pod borer (Maruca testulatis) which attacks the planting of mung beans in the generative phase is one of the plant pests (OPT) which is very detrimental and can pose a threat of crop failure. The Study on Development of Peach Borer Forecasting Forecast Model for Green Bean Plants aims to obtain a model of forecasting pod borer on green beans carried out in May to December 2019 on 20 stretches spread in Cirebon Regency which are spread in 2 sub-districts (Susukan and Ciwaringin) respectively 10 (ten) overlays. In each sample field, 30 (thirty) sample plants were divided into 3 natural plots of 10 sample plants each, which were determined systematically at random. Observations were made visually by counting the number of pods and the number of symptomatic pods in each sample plant. To get the pod borer attack forecasting model, an analysis using linear regression analysis method was performed. The intensity of pod borer attack during the second harvest (9 MST) was significantly affected by the intensity of the attack at the beginning of pod formation (7 MST) and the attack forecasting model was as follows: Y = 10.98 X + 2.36 (r² = 0.65 ; Sig F = 5.79E-06), where Y = Intensity of Pod Borer attack at the age of 9 MST; X = Intensity of Pod Borer attack at the age of 7 MST. The model of forecasting the intensity of pod borer attack and the number of larvae is as follows: Y = 2.4146x + 2.7987; R2 = 0.7639; N = 13; Sig = 9.38E-05; where (X) is the number of larvae populations at week 7 and (Y) is the intensity of pod attack pests at the age of 9 MST.